EDUKASI SANTRI PONDOK PESANTREN IMAM SYAFI’I GENTENG BANYUWANGI MENGENAI CARA ANALISIS KANDUNGAN BORAKS MENGGUNAKAN KUNYIT - Eka Yunita Wulandari; Adisa Oktafiani; Sinta Nuriyah Putri Ayu (As-Sidanah, 2022)
Borax (Na2B4O7.10H2O) is white crystals, odorless, thermostable substance and a derivative of Boron. Borax is used to preserve wood, braze metal, and kill cockroaches. Unfortunately, borax is misused as a food preservative. Borax testing in the laboratory is carried out using chemicals and laboratory equipment that most people do not have. Turmeric can be used as a borax indicator because it contains curcumin which can react with borax. It is important to educate people about the dangers of borax in food and to test the borax in food using turmeric. This activity was carried out through a lecture, participatory learning, and discussion. The activity began with a lecture; practical demonstration and hands-on using turmeric juice, turmeric paper, and a toothpick with turmeric infuse; and discussion. The results of the questionnaire showed that this activity improved understanding about the danger of borax, borax test method in the laboratory, and a simple borax test using turmeric. It was concluded that the knowledge of the students of the Imam Asy-Shafii Islamic School on the dangers of borax was increased. The students were able to practice the analysis of borax content in food using turmeric. It was expected that the students and caregivers of Islamic boarding schools can use turmeric to select borax-free foods to ensure the food quality.